2022
DOI: 10.29333/ejmste/12559
|View full text |Cite
|
Sign up to set email alerts
|

The association between the gender gap in science achievement and students’ perceptions of their own attitudes and capabilities

Abstract: Among the countries that participated in the trends in international mathematics and science study (TIMSS) 2019 for grade 8 science, Oman had the highest gender gap in favor of girls. The current study explores the gender gap in science achievement in Oman and relates it to students’ varying perceptions of their own attitudes and capabilities. The sample in the study comprised 467 grade 9 students, 266 female and 201 male. The participants were given a TIMSS-like science test, along with four self-perception s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…However, Aurah (2017) employed MANOVA to examine science self-efficacy in terms of gender and detected a statistical difference, with female students reporting better self-assessment than male students. The same result was revealed by Al-Balushi et al (2022) indicating that there is a gender gap in science achievement, which is The study further shows the SC scores based on gender revealed no significant differences. It suggests that no statistical disparity can be identified between male and female in terms of their SC scores.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, Aurah (2017) employed MANOVA to examine science self-efficacy in terms of gender and detected a statistical difference, with female students reporting better self-assessment than male students. The same result was revealed by Al-Balushi et al (2022) indicating that there is a gender gap in science achievement, which is The study further shows the SC scores based on gender revealed no significant differences. It suggests that no statistical disparity can be identified between male and female in terms of their SC scores.…”
Section: Discussionsupporting
confidence: 66%
“…Gender gaps research in science has been investigated multiple times in the literature (i.e. Makarova, 2019;Charlesworth & Banaji, 2019;Huang et al, 2020;Sá et al, 2020;Al-Balushi et al, 2022;Cimpian et al, 2020;Meinck & Brese, 2019;Nygaard et al, 2022;Frandsen et al, 2020;Gupta, 2019;Reinking & Martin, 2018;Kiran et al, 2023;Marescotti et al, 2022). Makarova et al (2019) contended that genderscience stereotypes of math and science can possibly impact young women and men's goals to register in a STEM major at university by showing that a less definite masculine image of science has the potential to increase the probability of STEM career aspirations.…”
Section: Introductionmentioning
confidence: 99%